Analysis, by Simulation, of shear stresses on the Surface of Iris, in Presence of Intraocular Factor Lenses - Ramírez-Honorato, J. L.; Escobar-Del Pozo, C.; Rocha-Medina, J. A. (Revista Mexicana de Ingenieria Biomedica, 2018)
The study presents a methodology to evaluate intraocular phakic lenses, considering asymmetric aqueous humor flow due to modified conditions of the fluid outlet area. The main objective is to determine the effect of asymme-tries on shear stresses with and without phakik lenses. A finite element numerical simulation was developed using the eye geometry proposed by Repetto et al., [6]. The numerical method was tested with the results obtained by Tychsen et al., [8], giving results of the same order of magnitude. Velocity profiles, pressure distribution and shear stress at the solid boundaries are shown. The model does not take into account temperature variations. Therefore no buoyancy effects were considered. The results show that the induced asymmetries have a significant impact on aqueous humor velocity and on shear forces; however the shear stresses are not sufficient to cause cell detachment so the lens can be considered as harmless.